Development of Traditional Charcoal Burning Process into Innovative Community Prototype of Smokeless Village to Improve Quality of Life with Bio-Circular-Green Economy - แก้วพวง เทอดเกียรติ; เฮงศรีสมบัติ จิระศักดิ์; YONGPHET, PIYAPHONG (RMUTL Journal of Socially Engaged Scholarship, 2024)
This research is characterized as academic work for society that has researched a truly participatory process that leads to solving spatial problems through partnerships between researchers and communities. The main objective of this research is to reduce smoke problems caused by traditional charcoal burning in the area of ​​49 charcoal burning farmers in the Ban Khlong Arang area. Sa Kaeo Province This research is divided into 6 steps: 1. go to the area to study the community context 2. study innovation and technology ready for use 3. transfer innovation and technology 4. develop the potential of community innovators 5. analyze and summarize results with the community and 6 . Deliver and expand results in the area From the research, a charcoal kiln has been designed and built that has the distinctive feature of using an air flow system through a narrow channel at the base of the stove and the mouth of the stove, creating a flow and filling of air that results in complete combustion, reducing the occurrence. Smoke from incineration results in low smoke emissions. and burning with a pyrolysis process that seals gases in the wood. There are 40 community kilns, replacing and reducing the use of traditional charcoal kilns, resulting in less smoke emissions that pollute the community. Charcoal obtained from burning eucalyptus wood and acacia wood in the new stove can absorb 284.13 mg/g and 288.55 mg/g of iodine, respectively. In addition, a network of cooperation can be created to become a model. Future renewable energy learning center.